2023
DOI: 10.1200/op.22.00471
|View full text |Cite
|
Sign up to set email alerts
|

Care Fragmentation, Faulty Communication, and Documentation Lapses Derail a Treatment Plan

Abstract: This is the second Cancer Morbidity, Mortality, and Improvement Rounds, a series of articles intended to explore the unique safety risks experienced by oncology patients through the lens of quality improvement, systems and human factors engineering, and cognitive psychology. This case describes the care of a patient who was diagnosed with locally advanced lung cancer during the COVID-19 pandemic; it highlights how gaps in communication and care coordination caused the patient to receive care that did not refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Research has found that there is a premium on coordination with the core member(s) of a team 27 and among core team representatives in more complex MTS arrangements, such as AYA multidisciplinary teams (Wolfson), 28 main and community affiliate sites in the same health care system (Roberts). 29,30 Mechanisms such as the interoperability of health information technology 31 and dedicated program coordinators with integrated screening tools have shown promise (Fleege), 32 whereas the colocation of multidisciplinary care versus serial care (Majumdar, Smeltzer) 33,34 and other structural arrangements (O'Malley) 35 have yielded mixed results.…”
Section: What Needs To Be Coordinated By Whom?mentioning
confidence: 99%
“…Research has found that there is a premium on coordination with the core member(s) of a team 27 and among core team representatives in more complex MTS arrangements, such as AYA multidisciplinary teams (Wolfson), 28 main and community affiliate sites in the same health care system (Roberts). 29,30 Mechanisms such as the interoperability of health information technology 31 and dedicated program coordinators with integrated screening tools have shown promise (Fleege), 32 whereas the colocation of multidisciplinary care versus serial care (Majumdar, Smeltzer) 33,34 and other structural arrangements (O'Malley) 35 have yielded mixed results.…”
Section: What Needs To Be Coordinated By Whom?mentioning
confidence: 99%
“…Roberts et al 4 report a compelling case study that highlights the pitfalls of over-reliance on technology to support cancer care teams. The case highlights how increased reliance on technology tools and virtual communication methods has suppressed mainstays of high-quality cancer care, including interdisciplinary tumor boards, role clarification, team sensemaking, 5 and closed-loop communication.…”
mentioning
confidence: 99%